Collecting and Applying Usability Data from Distance Learners. Issue 1 (2nd January 2017) - Mitchell, Emily; West, Brandon
ABSTRACT: Growth of their college's off-campus and online course offerings led librarians at SUNY Oswego to run usability tests with off-campus students to compensate for a lack of responses from this population during earlier usability testing. Constraints on testing with off-campus students included lack of funding and librarian time, as well as difficulty in attracting student participation. A brief usability study that could be completed by students in the first 10 minutes of class was devised, consisting of a first click test, a survey question, and a top task analysis activity. The study was conducted with 22 students from a satellite-campus Master's in Education program. Discussion includes selecting appropriate tests, analysis of study results, and application of data for improving Website design and information literacy instruction in an academic library.